2023
DOI: 10.6023/cjoc202212019
|View full text |Cite
|
Sign up to set email alerts
|

Merging Electron Transfer Activation with 1,2-Metalate Migration: Deoxygenative Silylation of Amides

Abstract: A direct deoxygenative silylation of amides with silylboronate reagents is developed in the presence of SmI2/Mg, affording a variety of high value-added α-aminosilane compounds in moderate to excellent yields with good functional group compatibility. The key to the success of this strategy lies in the merging of activation of amides induced by electron transfer with 1,2-metalate migration. The addition of Xantphos ligand can improve the reaction efficiency. The reactions are operationally simple and proceed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 115 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Notably, this reaction behavior of TMSCF 3 is much different from that disclosed in previous reports. Therefore, further optimization efforts were made to enhance the selective formation of 2a . Based on some seminal reports and our own studies that the use of catalytic amounts of an additive may greatly influence the reductive property of SmI 2 , we subsequently proceeded to screen a variety of additives. Under otherwise identical conditions, the use of 5.0 mol % of hexamethylphosphoramide (HMPA) or protic solvents such as methanol as an additive resulted in complete inhibition of the formation of the desired product (entries 2–3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, this reaction behavior of TMSCF 3 is much different from that disclosed in previous reports. Therefore, further optimization efforts were made to enhance the selective formation of 2a . Based on some seminal reports and our own studies that the use of catalytic amounts of an additive may greatly influence the reductive property of SmI 2 , we subsequently proceeded to screen a variety of additives. Under otherwise identical conditions, the use of 5.0 mol % of hexamethylphosphoramide (HMPA) or protic solvents such as methanol as an additive resulted in complete inhibition of the formation of the desired product (entries 2–3).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above results and our previous investigation, we tentatively proposed that the amide is first reduced in an SET process by SmI 2 to generate a Sm(III)-coordinated ketyl radical anion I , , which is reduced further to a Sm(II)-coordinated radical II ,, via a SET from Sm (Scheme d). The intermediate II could also be viewed as a resonance structure of Sm(III)-coordinated anion III (a carbenoid equivalent), which may generate an α-aminocarbene intermediate IV by deoxygenation .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Subsequently, a series of deoxygenative functionalization of amides induced by SmI 2 /Sm were developed. 27–32 In 1997, Ogawa group reported a single example of SmI 2 /Sm-mediated deoxygenative alkynylation of amides using HMPA. 33 We attempted the deoxygenative alkynylation of other amides and alkynes under these conditions, but the results showed that other types of amides and alkynes are not applicable to this SmI 2 system.…”
mentioning
confidence: 99%